Sidoarjo Students' Motivation in Using Tiktok as an Entertainment Media - Sari, Naely Anjar; Rochmaniah, Ainur (Procedia of Social Sciences and Humanities, 2024)
This study aims to find out the motivation of Sidoarjo students in using Tiktok as an entertainment medium. Using the theory of Uses and Gratifications, this study analyzed in-depth interviews with ten students from various universities in Sidoarjo. The research method used is qualitative descriptive, with data collection techniques through semi-structured interviews. Data analysis uses reduction techniques, data presentation, and conclusion drawn. The results of the study show that the main motivation for students to use TikTok is to obtain entertainment, information, and education. TikTok also plays a role in reducing stress, although negative impacts such as academic procrastination and feelings of envy have been found. This study confirms that social media users such as TikTok play an active role in choosing media according to their needs. This research is expected to be the basis for further research on the use of Tiktok can be used effectively in an educational and social context.